1991
DOI: 10.1002/jcb.240470105
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 selectively inhibits binding of TGF‐β1 to the type I TGF‐β1 receptor

Abstract: A low molecular weight inhibitor of TGF-beta 1 binding was detected in partially purified human platelet extracts by using Hep 3B hepatoma cells in the binding assays. The inhibitory protein was purified to homogeneity and was identified as platelet factor 4 on the basis of its amino acid sequence. TGF-beta 1 binding to Hep 3B cells was almost completely inhibited by 100 nM concentrations of platelet factor 4, but TGF-beta 1 binding to NRK 49F fibroblasts was inhibited only slightly. Affinity cross-linking exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It remains a possibility that TGF-P, inhibits cell growth differently in different cell types. We have shown that TGF-6, inhibits the growth of human Hep 3B hepatoma cells in a novel manner that causes them to lose attachment to tissue culture flasks [27]. TGF-P, does not appear to inhibit pRb phosphorylation in this cell type (Whitson, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…It remains a possibility that TGF-P, inhibits cell growth differently in different cell types. We have shown that TGF-6, inhibits the growth of human Hep 3B hepatoma cells in a novel manner that causes them to lose attachment to tissue culture flasks [27]. TGF-P, does not appear to inhibit pRb phosphorylation in this cell type (Whitson, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…Although essentially all cells have high affinity receptors that specifically bind TGF-P, it remains uncertain to what extent binding proteins on the cell surface contribute in neutralizing TGF-P but without receptor-mediated intracellular signaling. Such constituents could be a subspecies of heparin molecules or related proteoglycans as betaglycan [35, 361, or proteins as platelet factor 4 that inhibit TGF-Pl binding to its type I TGF-P1 receptor [37]. It has been reported that the presence of serum is a requirement for the ability of SF + IL-I 1 to initiate colony formation in bone marrow cells from post-5-FU mice [ 1 11.…”
Section: Discussionmentioning
confidence: 99%
“…PF4 has been proposed to exert procoagulant activity by preventing the formation of the stable heparin-antithrombin III-thrombin ternary complex (2). It also inhibits binding of heparin-binding growth factors such as basic fibroblast growth factor, vascular endothelial growth factor (splice variant 165), and transforming growth factor ␤1 to their receptors (3)(4)(5) and is antiangiogenic, having been shown to inhibit proliferation and migration of endothelial cells in vitro (6). Subsequent studies demonstrated the ability of PF4 in vivo to specifically bind to areas of active angiogenesis (7) and to inhibit the growth of murine melanoma and colon carcinoma, probably as a result of suppressing tumor-induced neovascularization (8,9).…”
Section: Platelet Factor 4 (Pf4)mentioning
confidence: 99%